PENGEMBANGAN MODEL PEMBELAJARAN INOVATIF BERBASIS TEKNOLOGI INFORMASI DAN KOMUNIKASI (TIK) SESUAI KURIKULUM 2013 - Ade Koesnandar (Balai Besar Guru Penggerak Jawa Timur, 2020)
This research is a development research that is intended to produce innovative ICT-based learning development service models that are in line with the 2013 Curriculum through distance assistance. Based on the preliminary survey, it was obtained that teachers still face many difficulties in applying innovative learning models. This condition is the reason for the importance of this research. The development steps include: needs analysis, design, preparation of materials, making examples of lesson plans, application development, and application trials. From the results of the needs analysis, it was found that (1) in general teachers had tried to apply innovative learning models according to the demands of the 2013 curriculum even though they were still experiencing difficulties, (2) there was still a lack of examples and training in the implementation of innovative learning models caused the teacher's weak understanding of the concept innovative learning, (3) teachers still need additional knowledge and guidance in the application of innovative learning, (4) teachers also declare they are ready to utilize innovative learning assistance applications if available, and (5) teachers of Learning House Ambassadors (DRB) state their readiness to help other teachers overcome the difficulties of developing innovative learning models. In this research development, innovative learning development tutorial materials have been produced, both in the form of text and video media, examples of innovative lesson plans, and application 01 version of innovative learning assistance services that can be accessed via the website; sibatik.kemdikbud.go.id/inovatif. Penelitian ini merupakan penelitian pengembangan yang dimaksudkan untuk menghasilkan model layanan pengembangan pembelajaran inovatif berbasis TIK yang sesuai Kurikulum 2013 melalui pendampingan jarak jauh. Berdasarkan survei awal diperoleh informasi bahwa para guru masih banyak menghadapi kesulitan dalam menerapkan model-model pembelajaran inovatif. Kondisi yang demikian inilah yang menyebabkan pentingnya dilaksanakan penelitian ini. Langkah-langkah pengembangan mencakup: analisis kebutuhan, perancangan, penyiapan bahan, pembuatan contoh rencana pelaksanaan pembelajaran (RPP), pengembangan aplikasi, dan uji coba aplikasi. Dari hasil analisis kebutuhan diperoleh informasi bahwa (1) secara umum guru sudah berusaha menerapkan model pembelajaran inovatif sesuai tuntutan Kurikulum 2013 sekalipun masih mengalami kesulitan, (2) masih dirasakan kurangnya contoh-contoh dan pelatihan implementasi model pembelajaran inovatif menyebabkan masih lemahnya pemahaman guru terhadap konsep pembelajaran inovatif, (3) guru masih memerlukan tambahan pengetahuan dan bimbingan dalam penerapan pembelajaran inovatif, (4) guru juga menyatakan siap untuk memanfaatkan aplikasi pendampingan pembelajaran inovatif apabila tersedia, dan (5) guru Duta Rumah Belajar (DRB) menyatakan kesiapannya membantu guru lainnya mengatasi kesulitan mengembangkan model-model pembelajaran inovatif. Dalam penelitian pengembangan ini telah dihasilkan bahan tutorial pengembangan pembelajaran inovatif, baik dalam bentuk teks maupun media video, contoh-contoh RPP inovatif, dan aplikasi versi 01 layanan pendampingan pembelajaran inovatif yang dapat diakses melalui laman; sibatik.kemdikbud.go.id/inovatif.